(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
We investigated intra-species variation in the recruitment patterns of leaves of the plant species occurring at two different elevations in the central Himalaya. Plant species varied according to the growth forms i.e. evergreen and deciduous. Deciduous species showed earlier leaf emergence but shorter leaf longevity while in contrary evergreens responded with late emergence of leaves but retained leaves for longer duration. With decrease in temperature, leaf emergence tends to get delayed. Indirectly, our results allude to the resource acquisition by deciduous in contrary to evergreens adopting resource conservation. The divergent strategies may support stable coexistence of plant species.